Immunoparesis and polyclonal immunoglobulin recovery after auto-SCT for patients with multiple myeloma treated at a single institution. Issue 8 (3rd August 2018) - Jimenez-Zepeda, Victor H.; Duggan, Peter; Neri, Paola; Chaudhry, Ahsan; Tay, Jason; Bahlis, Nizar
Abstract: Immunoparesis and polyclonal immunoglobulin recovery have been recently described as common indicators of immune dysfunction in patients with multiple myeloma. In the present study, we aimed to assess the impact of immunoparesis and polyclonal immunoglobulin recovery at day-100 post autologous stem cell transplant (auto-SCT) on clinical outcomes. A total of 302 patients were included for the analysis of immunoparesis, and 197 were evaluable for polyclonal immunoglobulin recovery evaluation. Immunoparesis was observed in 93.5% of cases, with 47% of cases having polyclonal immunoglobulin recovery at 12 months post auto-SCT. Median overall and progression-free survival were longer in the group of patients with complete or partial normalization of polyclonal immunoglobulins. Patients receiving consolidation had a lower level of polyclonal reconstitution. In conclusion, polyclonal immunoglobulin recovery by 12 months post-auto-SCT is associated with superior overall and progression free survival in patients with MM. Efforts to better enhance polyclonal recovery deserve further investigation.